The Efficacy of Adalimumab as an Initial Treatment in Patients with Behçet’s Retinal Vasculitis - Yang, Shizhao; Huang, Zhaohao; Hu, Yunwei; Zhang, Jian; Liu, Xiuxing; Li, He; Xie, Lihui; Wen, Feng; Liang, Dan; Su, Wenru (Frontiers in Pharmacology, 2021)
Background: No study has evaluated the effectiveness of adalimumab (ADA) as first-line in treatment-naïve patients with retinal vasculitis due to Behçet's Uveitis (BU). Objective: To compare the efficacy of ADA plus conventional therapy and conventional therapy alone as initial treatments in naïve BU patients characterized by retinal vasculitis. Methods: Medical records of BU patients characterized by retinal vasculitis treated with conventional therapy (CT, refers to glucocorticoid and immunosuppressive agents) alone or ADA plus conventional therapy with at least 6 months of follow-up between February 2015 and June 2020 were analysed. Only patients who were first diagnosed with BU without previous systemic treatment were reviewed. The retinal vasculitis score based on fluorescein angiography (FA), best-corrected visual acuity (BCVA), glucocorticoid-sparing effect, the number of relapses and ocular complications were evaluated. Results: A total of 45 patients (87 eyes) were included. Twenty-four patients (55.33%) in the CT group were treated with conventional therapy and 21 patients (46.67%) in the ADA group were treated with ADA plus conventional therapy. The inflammatory parameters improved in both groups. FA scores showed significantly greater improvement in ADA group than CT group (P<0.001). The median number of relapses was significantly lower, and the duration of remission was longer in ADA group than CT group (P<0.001). At the last visit, a significantly better BCVA improvement (P=0.024), better inflammation control (anterior chamber inflammation P=0.017 and vitritis P<0.001) and lower daily glucocorticoid dosage (P=0.005) were identified in patients received ADA therapy. In CT group, 1 patient suffered hepatitis B and tuberculosis, 1 had growth retardation, 1 patient had with osteoporosis, then followed by other mild AEs (mostly respiratory upper tract infections); while in ADA group, 1 patient experienced a mild pneumonia (n=1) while milder AEs were represented mostly by respiratory upper tract infections followed by gastrointestinal discomfort. Conclusions: ADA plus conventional therapy achieved superiority over conventional therapy as initial treatment in naïve BU patients with retinal vasculitis.